Factors Causing the Students’ Problems in Listening Skills at The Eight Semester of English Study Program of Madako University - Nurfad; Moh.Firmansyah; Ismail Yunus H; Jaya (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
The purpose of this study was to determine the factors causing students to experience difficulties in listening skills in the eighth semester English Language Study Program, Madako University. In this study, the researcher focused on the factors that hinder students in listening skills, including how students overcome these obstacles. The respondents of this study were eighth semester English Language Study Program students, Madako University. This study is a qualitative descriptive study where the researcher collected data using direct interview techniques. To obtain data and research results from students who were sources based on the researcher's findings, several factors were found that caused problems for students in the listening skills process. Namely 1. Cultural Differences, 2. Quality of Recording Materials, 3. Unfamiliar Vocabulary, 4. Length and Speed ​​of Listening, 5. Physical Condition, 6. Noise-Related Problems, 7. Lack of Concentration.